Comparison of stressful life events among family caregivers of cancer, mental retardation and schizophrenia patients leading to stress, anxiety and depression and its effect on quality of life - Sharma, Sandeep; Rathi, Anant K.; Verma, Kamal K.; Bishnoi, Divya (International Journal of Research in Medical Sciences, 2020)
Background: Mental retardation (MR), schizophrenia and cancer are chronic disorders, requiring long term treatment along with family support. Principal caregiver is usually nonprofessional family person who play a pivotal role in supporting the patient medically, emotionally and financially which in turn affects their own health and quality of life. To identify stressful life events, level of anxiety, stress, depression and Quality of life in these family caregivers (FC), this study was planned. Methods: After gaining consent, the FC were assessed on Presumptive Stressful Life Events Scale (PSLE), Depression Anxiety Stress Scale (DASS) and WHO Quality of Life -Bref Scale (WHOQOL-Bref). Data so gained was analyzed by SPSS-21 and results were drawn. Results: 66 FC of cancer patients, 39 FC of MR patients and 53 FC of Schizophrenia patients were assessed. All three groups were found to be matched socio-demographically. On PSLE Mean of total stressful life events for cancer FC was 7±1.5, for MR 6.02±1.5 and for schizophrenia FC was 5.75±1.70 and this difference was statistically significant. Mean of total undesirable life events was 5.31±1.3, 4.33±1.34 and 3.86±1.46 respectively and this difference was also statistically significant. Similarly difference in mean stress score of total life events and for undesirable events was also statistically significant. On DASS scale no statistically significant difference was found within the groups. Quality of life was significantly low depicting high impact on physical health and social life of these care givers. Conclusions: Family Caregivers of cancer, mental retardation and schizophrenia groups are highly affected and there is urgent need to address these issues for early diagnosis and treatment.